Analisis Efektivitas Aplikasi E-Samsat sebagai Sarana Pembayaran Pajak dengan Metode Eucs - Rizal Ependi; Sofiansyah Fadli (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The purpose of this study is to assess how effective. of the e-Samsat application as a vehicle tax payment platform using the End-User Computing Satisfaction (EUCS) approach. The EUCS model evaluates five dimensions: content, accuracy, format, ease of use, and timeliness. Data collection was carried out by means of questionnaires provided to 33 participants who are e-Samsat users in Central Lombok. The analysis methods include convergent validity testing, AVE, discriminant validity, and construct reliability. The findings indicate an average overall satisfaction score of 3.68 out of 5, classifying the e-Samsat application as